Spectrophotometric Estimation of Trimethoprim By Charge Transfer Complex Formation Reaction - Theia'a N. Al-Sabha; A. W. Al-Azzawi (Pakistan Journal of Analytical & Environmental Chemistry, 2025)
A new simple method is proposed for the spectrophotometric estimation of trimethoprim drug (TMP), depending on the formation of an n-π charge transfer complex between TMP acting as n-donor and o-chloranil acting as π-acceptor in ethanolic medium. The complex has a maximum absorbance at 379 nm. Beer’s law is applied within the limits of concentration of 5–60 μg/mL. The method is accurate, precise, and sensitive, as the average recovery was 101.57%. The relative standard deviation (RSD) was less than 3.03%, and the molar absorptivity was 1.11×104 L/mol.cm. The limit of the quantitation (LOQ) was 0.2323 µg/mL, and the limit of detection (LOD) was 0.0697 µg/mL. The complex was formed at a ratio of 1:1. TMP is usually found mixed with sulfamethoxazole in its pharmaceutical preparations, so the uniqueness of this method over others is that TMP can be estimated alone in tablets containing sulfamethoxazole and other excipients after the simple extraction. The method was contrasted favorably with the British Pharmacopoeia by computing the t-exp and F-test and other literature methods.